Triple Deficits And The European Countries - Kang, Lei Cheng (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study empirically investigates the relationship between budget deficit, current account deficit and financial account deficit in European countries. Data are obtained based on yearly data from 1999 to 2014 for France, Romania and United Kingdom; 2005 to 2014 for Cyprus; and 2007 to 2014 for Albania, Armenia, Belarus, Georgia, Macedonia, Moldova, Montenegro and Turkey. Then, the data was converted from yearly to quarterly by using Eviews 8 and the results are tested based on quarterly data. The methodologies applied in this study are unit root tests, cointegration tests and Granger causality test. There are three conclusions in this study which are: first, the budget deficit, current account deficit and financial account deficit are stationary either in level form or first difference. Second, the cointegration tests results show that there are long run relationship between the triple deficit in Albania, Armenia, Belarus, France, Moldova, Montenegro, and United Kingdom. Third, the triple deficits have found in Albania, Armenia, Macedonia, and Turkey while Cyprus, Georgia, Romania and United Kingdom have the twin deficits problem in the short run.